Orientasi Pasar, Orientasi Kewirausahaan, Kapabilitas Pemasaran dan Kinerja Pemasaran - Hatta, Iha Haryani (Jurnal Aplikasi Manajemen, 2015)
Market Orientation, Entrepreneurship Orientation, Capability and MarketingPerformance. The aims of this study are to know the effect of market orientation and entrepreneurialorientation on the capabilities and marketing performance; and to know the effect ofmarketing capability on the marketing performance. This study uses 200 managers ofspecificcharacteristics of Indonesian restaurants in Jakarta as a simple random sampling. The dataanalysis was used structural equation modeling (SEM) and processed by employing lisrel8.5. This research concludes that although the market orientation and entrepreneurial orientationpositively affect the marketing capability, and marketing capability has a positiveeffect on the marketing performance, but the understanding of market orientation and entrepreneurialorientation does not directly affect marketing performance. Entrepreneurial orientationhas the most dominant influence path towards marketing capabilities and performancemarketing.